Production of succinic acid from glycerol and glycerol waste - Nor Hidawati, Elias (2012)
Succinic acid is extensively used globally for manufacture of synthetic resin, biodegradable polymer, pharmaceutical product and food flavoring. Traditionally, succinic acid produced through petrochemical route. The process is non-renewable and will affected pollution in the environment. Therefore, more attention has been focused towards a friendly environment processes for succinic acid production by way of fermentation process; which is highly recommended nowadays. In this research, studies been done to produce succinic acid through anaerobic fermentation of glycerol waste using Escherichia coli and to investigate the effect of each factors that influence succinic acid production. The most influential parameter for succinic acid production obtained via preliminary study of parameter range selection were glycerol concentration, tryptone concentration, sodium carbonate (Na2CO3) concentration , inoculums density, pH and incubation period. This experiment has produced 0.973g/l succinic acid using One-factor-at-a-time (OFAT) approach from commercial glycerol sample. These six variables screened to select the most significant factor affected succinic acid production using fractional factorial design (FFD) based on first order model term. Four factors selected while, two factors eliminated for the next stage of experiment. Subsequently, full factor central composite designs (CCD) falling under RSM employed to develop a mathematical correlation model between the significant factors for physio-chemical variables of succinic acid production. The experiment has produced 7.55g/l succinic acid from commercial glycerol sample. Besides, a second order polynomial regression fitted and the model was adequate by R-squared 0.9864. Meanwhile, under the optimum level, it is about 7.34g/l succinic acid being produced from commercial glycerol and 7.32g/l of succinic acid produced from recovered glycerol. Overall, this research shows glycerine pitch can be used safely and effective as a carbon source for Escherichia coli to produce succinic acid. In addition, this research provides an exciting opportunity to transform low-grade glycerine pitch into highly demanded chemical such succinic acid